A Multicenter, Randomized, Double-Blind, Split-Body Clinical Trial Evaluating the Efficacy and Outcomes of a Topical Product Pre and Post Aesthetic Surgical Body Procedures. (10th June 2022) - Casas, Laurie A; Claytor, R Brannon; Zeidler, Kamakshi R; Shridharani, Sachin M; Cohen, Steven R; Khanna, Julie J; Gould, Daniel J; Yates, Essie K; Lultschik, Shantel; Bell, Michaela; Widgerow, Alan D
Abstract: Background: Skin preconditioning prior to and following procedures, has previously been demonstrated to hasten and optimize healing, and decrease the symptoms and signs associated with invasive surgery. These trials involved the use of multiple topical products. In an effort to control costs and to increase patient compliance, a single surgical product was developed, with actives aimed at decreasing swelling, bruising, induration, and internal fibrous banding. Objectives: This multi-center trial was designed to measure the efficacy of this single product in these mentioned parameters. Methods: A double-blind, randomized, split body, clinical study was undertaken in 29 patients involving 38 surgical procedures. Assessments included photography, biopsies, ultrasound imaging, and blinded investigator and participant assessments. Results: Differentiated results between test comparator sides became apparent at postop day 10-14 (as previously observed). Thus, blinded investigator and participant assessment scores demonstrated statistical significance exclusive to the test product side at postop day 10-14 for ecchymoses and then extending to skin discoloration, edema, induration and subcutaneous fibrous banding, at weeks 3, 4, 6, and 12. Ultrasound evaluation confirmed the earlier dissolution of fibrous banding on the test side in the subcutaneous tissue at the 3-6-week postop period. In addition, biopsies assessing the pre-conditioned period prior to surgery confirmed that the topical test product stimulated a remodeled extracellular matrix without comparative changes on the opposite side. Conclusions: A single peri-surgical product designed for the use with invasive surgery produced significant differences in ecchymosis, skin discoloration, edema, induration and ongoing resolution of fibrous banding over many weeks. This study validation provides an additional adjunct to surgical procedures. Level of Evidence: 2: